Challenges in Completing the Study for Students of Elementary School Teacher’s Education - Sudarmono R, Muh Aidil; Martini, Martini; Bahjah, Dzata; Musa, Kemal Abu (Graduate Program Magister Manajemen Pendidikan, 2024)
The research aims to identify challenges in completing studies for students of the Islamic Elementary School Teacher Education program at the Faculty of Islamic Religion, Muslim University of Indonesia. The research employs observation, interviews, and documentation as its methods. in completing studies for students are both internal (e.g., lack of motivation leading to course delays) and external (e.g., economic limitations, social interactions, and academic disruptions). Efforts to address the challenges include providing motivation during free time, but specific measures are lacking. Recommendations involve collaboration with parents, regular meetings, specialized guidance, and continuous evaluation of instructors. The research on the completion of studies among students in the Islamic Elementary School Teacher Education program at the Faculty of Islamic Religion, Muslim University of Indonesia has uncovered critical insights into the challenges and contributing factors affecting study timelines. The study identifies internal factors such as a lack of motivation and external factors encompassing economic constraints, social influences, and academic disruptions. Furthermore, it sheds light on the average study duration of 7 years for some students, emphasizing the potential consequences on various aspects of their lives. The findings underscore the need for targeted interventions, including motivational strategies and collaborative efforts with parents, to address the multifaceted challenges hindering timely study completion. This research contributes valuable knowledge to the academic community, particularly in understanding and addressing the complexities associated with students’ progress in the Islamic Elementary School Teacher Education program.